2014
DOI: 10.1111/gcb.12635
|View full text |Cite
|
Sign up to set email alerts
|

A method for calculating a land‐use change carbon footprint (LUCCFP) for agricultural commodities – applications to Brazilian beef and soy, Indonesian palm oil

Abstract: The world's agricultural system has come under increasing scrutiny recently as an important driver of global climate change, creating a demand for indicators that estimate the climatic impacts of agricultural commodities. Such carbon footprints, however, have in most cases excluded emissions from land-use change and the proposed methodologies for including this significant emissions source suffer from different shortcomings. Here, we propose a new methodology for calculating land-use change carbon footprints f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 41 publications
(63 reference statements)
1
60
0
1
Order By: Relevance
“…We based this on the study by Prudêncio da Silva et al (2010). In the literature, however, the following assumptions were found: Van Middelaar et al (2013) used the same values; assumed that 100% of the soy expansion in Brazil directly occurs on forest land; Nemecek et al (in press) assumed that 12% of the soy produced in Central West Brazil comes from tropical forests and 38% comes from shrubland; Meul et al, (2012) assumed that 3% of the soy produced in Central West Brazil comes from tropical forests and 5% comes from shrubland; and Persson et al (2014) assumed that 2% of the soy produced in Central West Brazil comes from tropical forests and 12% comes from shrubland. Moreover, based on satellite data, it has been shown that, since 2006, deforestation rates in Brazil have decreased, and that since the late 2000s the contribution of soy production to deforestation has been minimal (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We based this on the study by Prudêncio da Silva et al (2010). In the literature, however, the following assumptions were found: Van Middelaar et al (2013) used the same values; assumed that 100% of the soy expansion in Brazil directly occurs on forest land; Nemecek et al (in press) assumed that 12% of the soy produced in Central West Brazil comes from tropical forests and 38% comes from shrubland; Meul et al, (2012) assumed that 3% of the soy produced in Central West Brazil comes from tropical forests and 5% comes from shrubland; and Persson et al (2014) assumed that 2% of the soy produced in Central West Brazil comes from tropical forests and 12% comes from shrubland. Moreover, based on satellite data, it has been shown that, since 2006, deforestation rates in Brazil have decreased, and that since the late 2000s the contribution of soy production to deforestation has been minimal (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies focusing on LUC emissions associated with agricultural production in Brazil have been published recently. Nevertheless, these have focused either at the whole country level (Flynn et al., ; Persson, Henders, & Cederberg, ) or for specific Brazilian states and regions (Figueirêdo et al., , ; Macedo et al., ; Maciel et al., ). Initiatives to monitor LUC on a regular basis are very recent (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On top of this comes increased demand for land to produce bioenergy and biofuels, driven by concerns for energy security and climate change. A successful long-term strategy for forest conservation therefore must contain, inter alia, elements of forest protection (i.e., raising the value of standing forests to counteract the increased profitability of clearing as land demand rises 23 ), measures to curb demand growth (e.g., inducing diet shifts away from animal products or limiting demand for bioenergy 24 ), and demand-side policies that aim to steer agricultural expansion away from sensitive ecosystems, such as natural forests.…”
Section: Fig 1: Carbon Dioxide (Co 2 ) Emissions From Deforestation mentioning
confidence: 99%
“…11,26 Timber extraction from natural forests has been, and still is, a dominant driver of deforestation in Southeast Asia, but both shifting cultivation and plantation agriculture (e.g., rubber) have also played important roles. In recent years the latter, in the form of oil palm and short rotation timber plantations for pulp and paper production, have gained in importance as deforestation drivers, especially in Indonesia 24,29,30 .…”
Section: Country-commodity Casesmentioning
confidence: 99%
See 1 more Smart Citation